Different doses of sodium monensin on feedlot performance, carcass characteristics and digestibility of Nellore cattle - Stefano Pereira, Murillo Ceola [UNESP]; Nagatani Rigueiro, Andre Luiz [UNESP]; Oliveira, Cassiele Aparecida de; Gomes de Soutello, Ricardo Velludo [UNESP]; Arrigoni, Mario de Beni [UNESP]; Millen, Danilo Domingues [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2019)
The objective of this study was to determine the effects of different doses of sodium monensin on feedlot performance, carcass characteristics and nutrient digestibility of Nellore cattle. The experiment was designed as a completely randomized block, replicated 12 times, in which 60 20-months old yearling Nellore bulls (402.52 +/- 33.02 kg) were fed in individual pens for 84 days according to the different doses of monensin expressed in ppm (dry matter basis): 0, 9, 18, 27 and 36. As doses of monensin increased, final body weight, average daily gain, gain-to-feed ratio, and dressing percentage were affected cubically (P < 0.03), where animals fed 9 ppm of monensin presented greater average daily gain and better gain-to-feed ratio. Likewise, as dose of monensin increased, dry matter intake, hot carcass weight, and neutral detergent fiber and fecal starch digestibility in finishing period decreased linearly (P < 0.05). In addition, neutral detergent fiber digestibility in adaptation period in creased linearly (P = 0.01) as doses of monensin increased. Thus, based on the results of this study, if monens in is going to be included in finishing diets for feedlot Nellore cattle, the dose of 9 ppm should be considered as the most feasible option.
Keywords: additive; ionophore; starch; NDF; Zebu